1994
DOI: 10.1002/adma.19940060104
|View full text |Cite
|
Sign up to set email alerts
|

Ring‐Opening Polymerization and ring‐closing depolymerization

Abstract: Ring‐opening polymerization (ROP) of cyclic monomers is most suitable for the preparation of sequential copolymers of the type (AAB)n, the sequence being determined by the structure of the monomer. The thermodynamics and mechanisms of ROP are reviewed, including radical, cationic, anionic, and metathetical ROP, with may examples being given. As recycling becomes more important, interest in reversible polymerization, i.e., depolymerization, is increasing. The results available so far on the depolymerization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 103 publications
0
53
0
Order By: Relevance
“…The reaction scheme and the adopted synthetic procedure for Al(Osec-Bu) 3 as initiator in toluene solution have previously been reported. [1,9] In a typical polymerization, e. g. the one used to synthesize a diblock copolymer containing 70 wt.-% of DTC (sample 2), 100 ml of a 0.77 m solution of DTC in toluene at 20 8C was initiated with 1.14 ml of Al(Osec-Bu) 3 dissolved in the same solvent ([I] 0 = 3.38 mmol/l) and polymerized in an inert gas atmosphere. After 80 min, 1.92 g of CL (13.5 mmol) were added and the system was left to polymerize at 80 8C.…”
Section: Synthesis Of the Copolymersmentioning
confidence: 99%
See 2 more Smart Citations
“…The reaction scheme and the adopted synthetic procedure for Al(Osec-Bu) 3 as initiator in toluene solution have previously been reported. [1,9] In a typical polymerization, e. g. the one used to synthesize a diblock copolymer containing 70 wt.-% of DTC (sample 2), 100 ml of a 0.77 m solution of DTC in toluene at 20 8C was initiated with 1.14 ml of Al(Osec-Bu) 3 dissolved in the same solvent ([I] 0 = 3.38 mmol/l) and polymerized in an inert gas atmosphere. After 80 min, 1.92 g of CL (13.5 mmol) were added and the system was left to polymerize at 80 8C.…”
Section: Synthesis Of the Copolymersmentioning
confidence: 99%
“…[1] It was shown that copolymerization of dimethyltrimethylene carbonate (DTC) with a variety of cyclic as well as linear comonomers yields random, tapered or block copolymers depending on initiator, comonomer nature, and reaction procedure. [2,3] Block copolymers were successfully obtained by DTC polymerization, initiated by polymeric hydroxytelechelic precursors or by living chains of the comonomer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ring-opening polymerization discloses an alternative route to polymers which are typically obtained by polycondensation or polyaddition polymerization following a step growth mechanism. [1,2] The present paper is devoted to the ring-opening polymerization of heterocycles like cyclic carbonates, lactones, lactams, cyclic amide-esters, urethanes, and ureas by means of ionic and insertion type initiators and covers mostly the authors' own work. Copolymerization of the above mentioned monomers results in random, sequential, block and alternating copolymers depending on the initiator used and the polymerization conditions applied.…”
Section: Introductionmentioning
confidence: 99%
“…According to time dependent1 H NMR analysis in the beginning only LLA-LLA diads are observed, i. e. first LLA is polymerized. With the elapse of time triads comprising one DTC and two LLA units are formed, then triads with two DTC and one LLA unit and finally DTClactate-DTC and DTC-homotriads are formed.…”
mentioning
confidence: 99%